A stepwise approach based on a rational use of components separation and double mesh prosthesis for incisional hernia repair - Celdran, Angel; Fraile, M. J.; Georgiev Hristov, Tihomir; González Ayora, Santiago (My University, 2015)
Purpose We aimed to evaluate the results of a protocol for a tension-free reconstruction of the abdominal wall in midline incisional hernia repair, based on the rational association of components separation and prosthesis, independently of the hernia size. Methods A total of 100 consecutive patients with midline incisional hernias were prospectively included in the study. Three groups according to the transverse diameter of the defect [group A (<4 cm, N = 18), group B (4¿10 cm, N = 59), and group C (>10 cm, N = 23)] were identified. Results Components separation was necessary in 54 % of the patients: 16.7 % (3/18) in group A, 59.3 % (35/59) in group B, and 69.6 % (16/23) in group C. Complete tension-free reconstruction was achieved in 87 % of the patients: 94.4 % (17/18) in group A, 91.5 % (54/59) in group B, and 69.6 % (16/23) in group C. Overall morbidity rate was 21 % (21/100) [group A 16.7 % (3/18), group B 22 % (13/59), and group C 21.7 % (5/23)]. Hospital length of stay was 3.7 ± 3.3 days (group A 1.83 ± 1.43 days, group B 3.05 ± 2.11 days, and group C 6.91 ± 4.45 days). Median follow-up was 25 months (interquartile range 12.25¿55.25) with overall recurrence of 2 %. Conclusion A tension-free abdominal wall reconstruction can be achieved in most cases of small and large midline incisional hernia repair, by a stepwise approach based on a rational association of components separation and double mesh prosthesis, with a low morbidity and recurrence rates.